2012
DOI: 10.1002/oa.2299
|View full text |Cite
|
Sign up to set email alerts
|

Entheseal Changes and Functional Implications of the Humeral Medial Epicondyle

Abstract: Longitudinal rotation of the forearm (pronosupination) is an essential component of human manipulative tasks. The efficiency of this movement is dependent not only on the rotatory muscles but also on several morphological and structural features of the upper limb. In a recent study, we observed that the size and orientation of the humeral medial epicondyle played an important role in forearm rotatory ability. We further observed that the forearm muscular activity, specifically the motion of pronation, promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Although these papers emphasise important considerations and new methods, they are less theoretical than those in the previous sections and show a more practical use of EC. The first paper in this section (Ibáñez‐Gimeno et al , ) tests the relationship between pronosupination, as measured by the orientation of the humeral medial epicondyle and EC, to determine whether the orientation of this feature can be used as a marker of activity. The results found that the angle of the medial epicondyle increases the efficiency of the pronation range when the elbow is extended.…”
Section: A Brief Overview Of Papers In This Special Issuementioning
confidence: 99%
“…Although these papers emphasise important considerations and new methods, they are less theoretical than those in the previous sections and show a more practical use of EC. The first paper in this section (Ibáñez‐Gimeno et al , ) tests the relationship between pronosupination, as measured by the orientation of the humeral medial epicondyle and EC, to determine whether the orientation of this feature can be used as a marker of activity. The results found that the angle of the medial epicondyle increases the efficiency of the pronation range when the elbow is extended.…”
Section: A Brief Overview Of Papers In This Special Issuementioning
confidence: 99%
“…A more posteriorly oriented epicondyle, i.e. more retroflexed [5] , [30] , is associated with a greater E rot in full extension of the elbow, whereas an epicondyle with a lower degree of retroflexion has greater values of E rot in full flexion. Moreover, a more proximally oriented epicondyle enhances E rot in full flexion, whereas when it is more distally oriented, E rot increases in extension.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, a more proximally oriented epicondyle enhances E rot in full flexion, whereas when it is more distally oriented, E rot increases in extension. The orientation of the medial epicondyle was reported to present a partially activity-dependent plasticity, and so it was hypothesized that it can be modified to enhance certain abilities [30] . In this regard, and in agreement with the abovementioned relationship between E rot and epicondylar orientation, a simple observation of the upper-limb positioning shows that a habitual and continued contraction of PT in full elbow flexion would reorient the epicondyle towards a more proximal position.…”
Section: Discussionmentioning
confidence: 99%
“…The shape of the humeral medial epicondyle appears to have an influence on the pronationsupination range during elbow flexion and extension [115] . Among Upper Palaeolithic hunters, throwing has also been considered to be one of the main factors determining the remarkable degree of asymmetry in humeral mechanical rigidity, which is comparable or greater than that shown in professional tennis players or, indeed, throwers (e.g.…”
Section: Discussionmentioning
confidence: 99%